PENYULUHAN MENGENAI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA MASA PANDEMI COVID-19 DI DESA SINGOCANDI: Counseling On Clean And Healthy Living Behavior During The Covid-19 Pandemic In Singocandi Village - Heny Alpandari; Tangguh Prakoso; Hendy Hendro; Khairul Anwar; Nindya Arini; Winda Widyastuti; Muhamad Imanuddin (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Corona Virus or Covid-19 (Corona Virus Disease-19) has been defined by WHO (World Health Organization) as a new type of disease caused by infection with the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). Corona virus has a high transmission rate, and can cause death in the elderly and individuals with serious illnesses. Patients infected with the virus initially show symptoms like the common cold (fever, cough, runny nose, sore throat) muscle aches, headaches) but if not treated immediately will lead to severe symptoms such as diarrhea and pneumonia. Even some patients who have a history of comorbidities if they are infected can be at risk of death. The government has issued a policy in the form of a health protocol that must be implemented by every individual as a step to break the chain of transmission of Covid-19. One type of the protocol implements Clean and Healthy Living Behavior (PHBS). Singocandi Village is one of the villages located in Kota District, Kudus. The large number of community activities that residents participate in has the potential to spread the Covid-19 outbreak. The implementation of the Health protocol in Singocandi Village has not been fully implemented, this is due to a lack of information regarding how to apply the Health protocol properly and correctly. Based on the results obtained, the enthusiasm of the community from the extension activities was very good, this can be seen from the formation of clean and healthy behavior activities (PHBS) and the implementation of health protocols in every activity carried out in the midst of the Covid-19 pandemic